SURVEILANS KESEHATAN IBU DAN ANAK : STUDI PENGGUNAAN WAKTU BEKERJA BIDAN DESA DI KABUPATEN SORONG - , Sunarwan; , dr. Ova Emilia, Sp.OG (K), M.Med, PhD, ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Surveillance system in maternal and child health service by utilizing PWS KIA (local area monitoring of maternal and child health) able to help the available health service system. Village midwife has important role in the monitoring of maternal and child health in her work area. In the fact, information on local area monitoring of maternal and child health (PWS KIA) was not in time because the sending of the report from village midwife was often late, this because the village midwife was already busied by their daily task performing maternal and child health service and other health service. Objectives: To describe the utilization of work time by village midwife in performing local area surveillance of maternal and child health. Methods: This was descriptive study by combination of quantitative and qualitative approach (mixed method). As subject and sample was village midwife who was assigned in the village in the work area of Health Office of Sorong Regency. The number of sample was 34 midwifes, sampling was performed by exhaustive sampling (all of the population). Qualitative data was obtained by observation, archive review, and interview to identify further on the utilization of work time based on log book on daily activity of the respondent. Results and discussion: Out of 34 respondents, they used time work that was recorded in log book on daily activities between 14 to 30 work days in average was 21 work days with the utilization of work time about 88,670 minutes (average was 2,607 minutes) per respondent or 2 hours per day. Most time was used for maternal and child health (KIA) service that was about 51,275 minutes (57.8%) with average of 1,508 minutes (36.7%) with average was 957 minutes per respondent and time for activities documentation was 5,320 minutes (6.0%) with the average number of time was 156 minutes per respondent. Time utilization for KIA service includes a time for home visiting that was 8,475 minutes (16.5%) out of total time for maternal and child health service (MCH service) or in average per respondent used time for home visiting about 249 minutes. Bivariate analysis showed that time for home visiting had significant correlation to the coverage of delivery that was attended by health worker (Pn), RR value was 2 (95% CI: 0.98- 4.08) and p=0.04. It was also known that time for home visiting had significant correlation to the coverage of complete neonates visiting (KN). It was obtained RR= 2.17 (95%CI= 1.08-4.34) and p=0.02. Conclusion: Most of work time of village midwife was for maternal and child health (MCH) service. In the MCH service, includes times for home visiting that made great contribution to the increasing of the coverage of complete neonates visiting (KN).